Finite element modelling of thermal and moisture mapping of layered cricket helmets. Issue 2 (February 2023) - Guan, Z.W.; Dullah, A.R.; Wang, X.L.; Wang, Q.Y.
Abstract: This paper presents the development of numerical modelling to simulate thermal and moisture mapping of layered cricket helmets. The 3D laser scanning methodology was used to obtain geometrical data of a dummy human head with non-ventilated (NVL) and ventilated (VL) helmets to generate the meshes. Here, heat transfer and mass diffusion were applied in the finite element simulations to model the temperature and relative humidity (RH) distributions inside NVL and VL helmets, which were processed as the temperature-time and RH-time charts. The simulated results were validated against the corresponding experimental measurements with reasonably good correlation, in terms of the general trend on reginal temperature and RH against time, although parameters such as helmet movement and local sweating were not considered in the modelling to simplify the simulation. The discrepancies between the FE simulation results and the measurements are generally within 7% for in-helmet temperature and 5% for RH, for both types of helmets in the low ambient conditions (20 °C and 50% RH), although such the discrepancy is about 10% for the VL helmet subjected to the high ambient conditions (35 °C and 30% RH). The models developed are ready to be used for parametric studies on non-ventilated helmet to optimize the ventilation openings for improving the thermal comfort.